(untitled) (Colloquia Comparativa Litterarum, 2025)
The intertextual relation between Letters of a Portuguese Nun attributed to Guilleragues and New Portuguese Letters written by Maria Isabel Barreno, Maria Velho da Costa and Maria Teresa Horta is being analysed as an adaptation to the changing cultural conditions of the epoch. In the 17th-century version, the female figure goes through a process of egotistic revitalisation. The disaster of a love relationship, just like the shipwreck in Hans Blumenberg’s essay, leads to a radical individualisation and the conquest of solitude, a process that characterises the dawn of modern age. On the contrary, the adaptation of the same literary figure by the Portuguese feminist writers appears as a reaction against the solitude of women at the end of modernity. It is rather a “we” that is revitalised through a novel ‘couple experience’ or a community inhabiting a utopian “house of females”.